IMPACTION COLIC IN A THOROUGHBRED HORSE AND ITS MANAGEMENT - Giridharan Srinivasan; P. Pothiappan; G. Vijayakumar; G. Sathishkumar; S. Kavitha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Nine-year-old Indian Thoroughbred gelding was presented to the Large Animal Medicine Out-patient Unit of Madras Veterinary College Teaching Hospital with a history of restlessness, anorexia, not voided dung and urine, patchy sweating, flank watching, pawing, frequent lying down and getting up. Clinical examination of the animal revealed severe dehydration with tachycardia and absence of borborygmi on both sides of the abdomen. Rectal examination revealed scanty dry faeces in the rectum with distended caecum. Distended intestinal loops with the absence of intestinal peristalsis were observed through ultrasound examination. Haemato- biochemical examination revealed increases creatinine, creatine kinase and lactate dehydrogenase. The animal was treated with Inj. Ringer’s lactate and Inj. Flunixin meglumine. The animal was administered with liquid paraffin, magnesium sulphate, and simethicone along with the water through nasogastric intubation. Again the animal showed colic signs. Further the animal was sedated with xylazine and continuous rate infusion of Lignocaine @ 0.05mg/kg/min and fluids were administered through jugular catheter. The animal passed urine and showed a clinical improvement on following treatment. Animal started taking regular feed and voided dung on the third day of treatment.